2004
DOI: 10.1126/science.1101030
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Switch and Proton Wire Synchronize the Active Sites in Thiamine Enzymes

Abstract: Thiamine diphosphate (ThDP) is used as a cofactor in many key metabolic enzymes. We present evidence that the ThDPs in the two active sites of the E1 (EC 1.2.4.1) component of the pyruvate dehydrogenase complex communicate over a distance of 20 angstroms by reversibly shuttling a proton through an acidic tunnel in the protein. This "proton wire" permits the co-factors to serve reciprocally as general acid/base in catalysis and to switch the conformation of crucial active-site peptide loops. This synchronizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
186
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(203 citation statements)
references
References 33 publications
12
186
2
Order By: Relevance
“…There is no structural non-equivalence of the monomers detectable as observed for pyruvate dehydrogenase E1 component, for which a half-of-sites mechanism has been suggested ( Fig. S2) (24,25). The subunit structure of EcPOX (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is no structural non-equivalence of the monomers detectable as observed for pyruvate dehydrogenase E1 component, for which a half-of-sites mechanism has been suggested ( Fig. S2) (24,25). The subunit structure of EcPOX (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The major conclusion derived from structural, kinetic, and spectroscopic studies using substitutions at the Glu 235 , Glu 237 , and Arg 606 positions, residues that along with the highly conserved Glu 571 residue are hypothesized to form a communication pathway between the two active center ThDPs (2,3), is that ThDP binding in the second active center is affected by these substitutions according to the following observations. 1) Steady-state kinetic analysis revealed that ThDP binding is affected.…”
Section: Discussionmentioning
confidence: 99%
“…Communication between the thiamin diphosphate cofactors (ThDPs) 4 at the active centers of ThDP enzymes has been reported for several years (1)(2)(3)(4)(5)(6)). An intriguing pathway for such interaction had been suggested by Perham's group (2) on the basis of crystal structure studies on E1bs (the E1 component of the pyruvate dehydrogenase complex (PDHc) from Bacillus stearothermophilus).…”
mentioning
confidence: 99%
See 2 more Smart Citations